Compressive wideband spectrum sensing with spectral prior information - Daniel Romero; R. López-Valcarce; Geert Leus (Int. Conf. Acoust., Speech, Signal Process. (ICASSP), 2013)
Wideband spectrum sensing provides a means to determine the occupancy of channels spanning a broad range of frequencies. Practical limitations impose that the acquisition should be accomplished at a low rate, much below the Nyquist lower bound. Dramatic rate reductions can be obtained by the observation that only a few parameters need to be estimated in typical spectrum sensing applications. This paper discusses the joint estimation of the power of a number of channels, whose power spectral density (PSD) is known up to a scale factor, using compressive measurements. First, relying on a Gaussian assumption, an efficient approximate maximum likelihood (ML) technique is presented. Next, a least-squares estimator is applied for the general non-Gaussian case.
Keywords: cognitive radio; dynacs; spectrum sensing